2021
DOI: 10.3389/fcell.2021.710186
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Regulation of mRNA Translation and Ribosome Biogenesis During Germ Cell Development and Reproductive Aging

Abstract: The regulation of mRNA translation, both globally and at the level of individual transcripts, plays a central role in the development and function of germ cells across species. Genetic studies using flies, worms, zebrafish and mice have highlighted the importance of specific RNA binding proteins in driving various aspects of germ cell formation and function. Many of these mRNA binding proteins, including Pumilio, Nanos, Vasa and Dazl have been conserved through evolution, specifically mark germ cells, and carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 266 publications
(302 reference statements)
0
24
0
Order By: Relevance
“…Ribosomal proteins are overexpressed in breast cancer, liver, and colon [ 19 ]. Increased cell proliferation or development does not immediately increase ribosomal protein mRNA [ 20 ] immediately. In other words, there is valid proof that ribosomal proteins are likely to lead to cell's malignant transformation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal proteins are overexpressed in breast cancer, liver, and colon [ 19 ]. Increased cell proliferation or development does not immediately increase ribosomal protein mRNA [ 20 ] immediately. In other words, there is valid proof that ribosomal proteins are likely to lead to cell's malignant transformation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen phosphorylase catalyzed glycogen decomposition likely reduced the deleterious effects of glycogen overproduction on germ cells of fertile individuals [51]. BOLL belongs to the DAZ gene family, which is required to establish germ cell identity, regulate germ cell development, and prepare germ cells for entry into meiosis [52]. Our RNA sequencing assay showed that the downregulation of BOLL and its regulatory lncRNA MSTRG.5675.1 might particularly impact the gametogenesis process of oysters.…”
Section: Discussionmentioning
confidence: 87%
“…This results in discordance between mRNA and protein levels. Similarly, in various species, RA oocytes experience a decline in their ability to carry out mRNA translation [ 43 ]. The elevation in PEDF mRNA in RA GCs could derive from excessive transcription, as feedback to the decline in protein level.…”
Section: Discussionmentioning
confidence: 99%